And Zaccheus remained in the tree: Reconciliation and justice and the Truth and Reconciliation Commission - A Boesak (Verbum et Ecclesia, 2008)
And Zaccheus remained in the tree: Reconciliation and Justice and the Truth and Reconciliation Commission South Africas Truth and Reconciliation Commission (TRC) has been praised the world over for its work and its example is being followed by many countries, in Africa especially. In South Africa the TRC has raised hopes and expectations that went beyond the TRCs functionality within the framework of South Africas political settlement and its legal mandate given by Parliament. This contribution argues that there is growing disillusionment with the work of the TRC especially among black communities and that one of the major flaws of the TRC rests in its failure to link reconciliation with justice. Justice here must not be understood within the strict legal terms that some have applied to the work of the TRC but rather from within the expectations created by the TRC itself through its own insistence that its work should be seen as a Christian endeavour. This failure has a direct bearing on the situation South Africa finds itself in today, and the author argues that a return to an understanding of reconciliation that presupposes justice will help address one of the most critical issues in our social, political and theological discourse today.